Strategi Pengembangan Pegawai dalam Mewujudkan Profesionalisme Aparatur (Studi Pada Badan Kepegawaian Daerah Kota Batu) - Ansynesia, Ayu (Jurnal Administrasi Publik, 2015)
Abstract: Employee Development Strategy In Achieving Professionalism Apparatus (Study of Employee Development at Badan Kepegawaian Daerah (BKD) Kota Batu) Employee development may be required by BadanKepegawaian Daerah (BKD) Kota Batu in order to meet the demands of its organization both internally and externally. Relating to the functions of organization, professionalism Apparatus a central demand for BadanKepegawaian Daerah (BKD) Kota Batu. Apparatus Professionalism demands that have derived from the internal and external environment of the organization Badan Kepegawaian Daerah (BKD) Kota Batu. It is based on analysis using triangular theory of strategy Moore (2012), so it is known that to increase the operational component of capacity through staff development is a strategy that takes BKD Kota Batu in order to realize the professionalism apparatus. Employee development has been done BKD Kota Batu can be classified as On-the-job and off the job. With the dominance Off the Job, employee development activities are consistent BKD Kota Batu based mechanisms that have been set. However, with the success indicator borrow employee development methods have Hasibuan (2002) note that the indicators participants and facilities supporting factors BKD Kota Batu in implementing strategic development of its employees, while indicators curriculum (teaching materials), coach and fund the development of the inhibiting factor. Â  Keywords: Strategy, Employee Development, Professionalism Apparatus Â  Abstrak: Strategi Pengembangan Pegawai Dalam Mewujudkan Profesionalisme Aparatur (Studi pada Badan Kepegawaian Daerah Kota Batu) Pengembangan pegawai diperlukanâ€œBadan Kepegawaian Daerah (BKD) Kota Batuâ€ guna memenuhi tuntutan sebagai organisasi publik. Tuntutan-tuntutan tersebut ada yang berasal dari internal maupun eksternal lingkungan organisasi Badan Kepegawaian Daerah (BKD) Kota Batu. Hal ini didasarkan pada analisis dengan menggunakan teori segitiga strategi Moore (2012), sehingga diketahui bahwa melakukan peningkatan pada komponen operational capacity melalui pengembangan pegawai merupakan strategi yang dibutuhkan BKD Kota Batu agar dapat mewujudkan profesionalime aparatur. Pengembangan pegawai yang telah dilakukan BKD Kota Batu dapat diklasifikasikan menjadi On the job dan Off the Job. Dengan dominasi jenis Off the Job, kegiatan pengembangan pegawai BKD Kota BatuÂ  berjalan konsisten berdasarkan mekanisme yang telah ditetapkan. Namun, dengan meminjam indikator keberhasilan metode pengembangan pegawai miliki Hasibuan (2002) diketahui bahwa indikator peserta dan fasilitas menjadi faktor pendukung BKD Kota Batu dalam menjalankan strategi pengembangan pegawainya, sedangkan indikatorÂ  kurikulum, pelatih dan dana pengembanganÂ  menjadi faktor penghambatnya. Â  Kata kunci: Strategi, Pengembangan Pegawai, Profesionalisme AparaturÂ